Infrastructure for regional development - Sánchez, Ricardo J. (UN ECLAC SantiagoCL, 2012)
Examines different aspects of infrastructure in South America viz, connection between the provision of infrastructure services, economic development and equity and, reflects on the impact of infrastructure investment; offers an overview of infrastructure in the region, referring to both investment issues and economic infrastructure (energy, telecommunication, transport and sanitation); examines the regional integration of infrastructure and its importance and contains reflections in relation to the main infrastructure-related challenges in UNASUR countries.